Beyond imperial aesthetics : theories of art and politics in East Asia - Inoue, Mayumo; Choe, Steve (Hong Kong University Press, 2019)
Observing that the division between theory and empiricism remains inextricably linked to imperial modernity, manifest at the most basic level in the binary between 'the West' and 'Asia', the authors of this volume re-examine art and aesthetics to challenge these oppositions in order to reconceptualize politics and knowledge production in East Asia.